2020
DOI: 10.1159/000505191
|View full text |Cite
|
Sign up to set email alerts
|

How to Best Detect Portal Vein Tumor Thrombosis in Patients with Hepatocellular Carcinoma Meeting the Milan Criteria: Gadoxetic Acid-Enhanced MRI versus Contrast-Enhanced CT

Abstract: Introduction: The detection of portal vein tumor thrombosis (PVTT) in patients with hepatocellular carcinoma (HCC) meeting the Milan criteria is of critical importance as PVTT is known to be a contraindication to transplantation and an indicator of a dismal prognosis. Objective: To determine which modality may best detect PVTT, we compared the diagnostic performance of gadoxetic acid-enhanced MRI (GA-MRI) and contrast-enhanced CT (CECT) in HCC patients meeting the Milan criteria. Methods: We retrospectively en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 49 publications
(69 reference statements)
0
14
0
Order By: Relevance
“…Portal vein invasion was also less common in Japan than in other countries, but its incidence was higher than expected, occurring in 2,523 of 19,167 patients (13.2%) examined at the time of initial detection. This higher-than-expected incidence could be explained by recent advances in CT and MRI [51,52] and abdominal contrast-enhanced ultrasound [53], which have made minor vascular invasion graded as Vp1 or Vp2 clinically discernable from the time of initial detection for small HCCs.…”
Section: Introductionmentioning
confidence: 99%
“…Portal vein invasion was also less common in Japan than in other countries, but its incidence was higher than expected, occurring in 2,523 of 19,167 patients (13.2%) examined at the time of initial detection. This higher-than-expected incidence could be explained by recent advances in CT and MRI [51,52] and abdominal contrast-enhanced ultrasound [53], which have made minor vascular invasion graded as Vp1 or Vp2 clinically discernable from the time of initial detection for small HCCs.…”
Section: Introductionmentioning
confidence: 99%
“…For the detection of PVTT using the GA-MRI, Bae et al . reported that the additional information of diffusion- and T2-weighted imaging, which are not available with CECT, could contribute better depiction of common imaging findings, such as continuity with the tumor in the adjacent liver parenchyma than CE-CT [ 19 ], The study by Kim et al . demonstrated that the PVTT showed the increased T2 signal intensity and diffusion restriction, and the characteristic imaging features improved diagnostic capability [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The presence and extent of vascular invasion were diagnosed by characteristic findings using multiphase dynamic computed tomography (CT) or magnetic resonance imaging (MRI) [ 16 , 17 ]. Malignant tumor thrombus was defined as thrombus enhancement after the administration of contrast media compared to pre-contrast images (≥ 20 HU on CT and ≥ 15% on MRI), thrombus expansion within the involved vessel, and continuity of thrombus within the tumor [ 18 ].…”
Section: Methodsmentioning
confidence: 99%